Utilização da ferramenta PBC para controle do plano mestre de produção em uma indústria metalúrgica - Rodrigues, Vanessa Oliveira (2019)
Globalization has become a factor of competitive advantage by increasing competition among the organizations included in their respective markets. In view of this, organizations are looking for new techniques to gain competitive advantage, aiming to retain and attract new customers without affecting the financial area of the company. The competitive advantage a company can gain brings responsibility for all areas within the organization. Thus, this study seeks to deepen the area of planning and production control, more specifically in the planning and scheduling of orders. This activity is essential in order to have the resources available for production, it requires some time, knowledge and study. Encouraged by understanding the impact of this area within production and how it influences when it comes to determining production scheduling, considering the resources, activities, timing of operations involved, and the date of delivery to the customer. Thus, the present study seeks to present solutions proposals for the most appropriate application through the PBC order control system tool to control the Master Production Plan (MPS). Following this, the family of the products object of this study was defined and, through auxiliary tools and the information gathered from the process, it was possible to raise suggestions for improvements as actions to facilitate the production progress to move the finished material and also to present two suggestions from the company using the PBC method.